Blickpunkt Wissenschaft. Einige Bemerkungen zur journalistischen Wissenschaftsvermittlung - Makowska, Magdalena (Papers in Linguistics, 2019)
Popular-science magazines occupy an important place amidst numerous areas of journalistic activity. Their aim is to convey scientific knowledge that is easily digestible and attractive in its form also when it comes to non-specialists. Authors of such texts face a difficult task of reconciling what is typically scientific with what is journalistic. The purpose of the article is a media-linguistic analysis of phenomena which constitute the journalistic transfer of scientific knowledge, taking place both in the verbal as well as visual sphere. The research corpus is based on the texts published in the Polish edition of the popular science magazine FOCUS. In the centre of research interest there are processes of hybridization and differentiation which are employed by authors of multimodal texts in order to optimize the transfer of information.